Adolescent television viewing and unhealthy snack food consumption: the mediating role of home availability of unhealthy snack foods. Issue 2 (30th November 2012) - Pearson, Natalie; Biddle, Stuart JH; Williams, Lauren; Worsley, Anthony; Crawford, David; Ball, Kylie
Abstract Objective To examine whether home availability of energy-dense snack foods mediates the association between television (TV) viewing and energy-dense snack consumption among adolescents. Design Cross-sectional. Setting Secondary schools in Victoria, Australia. Subjects Adolescents (n 2984) from Years 7 and 9 of secondary school completed a web-based survey, between September 2004 and July 2005, assessing their energy-dense snack food consumption, school-day and weekend-day TV viewing and home availability of energy-dense snack foods. Results School-day and weekend-day TV viewing were positively associated with energy-dense snack consumption among adolescent boys (β = 0·003, P < 0·001) and girls (β = 0·03, P < 0·001). Furthermore, TV viewing (school day and weekend day) were positively associated with home availability of energy-dense snack foods among adolescent boys and girls and home availability of energy-dense snack foods was positively associated with energy-dense snack food consumption among boys (β = 0·26, P < 0·001) and girls (β = 0·28, P < 0·001). Home availability partly mediated the association between TV viewing and energy-dense snack consumption. Conclusions The results of the present study suggest that TV viewing has a significant role to play in adolescent unhealthy eating behaviours. Future research should assess the efficacy of methods to reduce adolescent energy-dense snack food consumption by targeting parents to reduce home availability of energy-dense foods and by reducing TV viewing behaviours of adolescents.